Design and environmental testing of imaging payload for a 6 U CubeSat at low Earth orbit: KITSUNE mission - Azami, Muhammad Hasif Bin; Orger, Necmi Cihan; Schulz, Victor Hugo; Oshiro, Takashi; Alarcon, Jose Rodrigo Cordova; Maskey, Abhas; Nakayama, Kazuhiro; Fukuda, Yoshiya; Kojima, Kaname; Yamauchi, Takashi; Masui, Hirokazu; Cho, Mengu; et al. (Frontiers in Space Technologies, 2022)
Earth observation (EO) missions remain a challenging task for small satellite platforms due to their demanding requirements and space environment effects. In this study, the camera payload development and mission requirements are presented together with the ground-based testing results for a 6U CubeSat called KITSUNE, operating at low Earth orbit. The major challenge of the payload development is maintaining the focus of the optical system despite the thermal vacuum environment in orbit since the low thermal capacity and rapid temperature variation of CubeSats hinder the camera focus. First, the payload is developed with an objective of a 5-m-class imaging mission, which has a 31.4 MP CMOS sensor and a lens with a 300-mm focal length. Second, polyimide heaters and multilayer insulators are utilized in order to maintain focus during imaging operations. Third, a collimator lens is used to aid in image capture during thermal vacuum tests. These images are analyzed thoroughly using various focus measure operators. The Diagonal Laplacian was found to be the most suitable operator due to the consistency in test results. The results also showed that the heat generated by the camera sensor significantly affects the lens temperature and, ultimately, the target temperature of the lens was defined at -1.8 degrees Celsius. Finally, the test results are discussed, including thermal vacuum, vibration, total ionization dose, and the effect of exposure to direct sunlight on the CMOS sensor.